From extraction to commercialization: an analysis of the timber supply chain in the brazilian legal amazon - de Souza, Dejanir José; Soliani, Rodrigo Duarte; Lima Junior, Francisco Bezerra de; Oliveira, Pollyana Rufino de Souza; Drumond, Thais Diniz Reis (JRG Journal of Academic Studies, 2023)
The production chain of the Brazilian forestry sector plays a crucial role in the global economy, providing a wide variety of products used in construction and industrial processes. The extraction of timber from native forests is essential for the production of paper, furniture, and charcoal, driving the economy through exports. However, the expansion of this sector faces challenges related to the lack of environmental conservation policies, infrastructure, financing, and the pressure of illegal deforestation. This article aims to enhance the description of the timber production process in the Brazilian Legal Amazon region, addressing its stages, procedures, and necessary considerations for sustainable extraction in accordance with environmental laws. A case study was conducted in a timber company in Porto Acre, Acre, involving literature review and a questionnaire administered to the responsible manager. The timber extraction process requires document analysis, legal compliance, and field surveys. Projects are developed to determine which tree species can be harvested, with a priority given to young trees and those with seeds, as well as considering protected areas. After project approval, camps and roads are set up to initiate the exploitation. The logistics involve the construction and maintenance of roads, temporary bridges, and storage yards, utilizing heavy machinery to clear paths, drag logs, and load trucks. The careful placement of storage yards considers biodiversity and ecosystem protection. Through a continuous commitment to responsible forest management, it is possible to reconcile economic activity with nature conservation, ensuring a sustainable future for native forests.